Substantiation of methods for the correction of vitamin D deficiency in children with juvenile idiopathic arthritis - N.S. Shevchenko; Yu.V. Khadzhynova (Zaslavsky O.Yu., 2020)
Background. Plenty of studies demonstrated the role of vitamin D in the pathogenesis of autoimmune diseases, including chronic childhood arthritis. Calciferol is able to suppress the immune response. Also, its deficiency is associated with increased activity of autoimmune diseases. The purpose of this study was: 1) to determinate vitamin D status in children with juvenile idiopathic arthritis (JIA) depending on the age of patients, variant of disease and therapy; 2) to analyze changes in the vitamin D status after its 3-month supplementation. Materials and methods. The study included 40 children with JIA (30 females, 10 males). Patients were divided into groups depending on the age, disease variant (oligo, -polyarticular variant, undifferentiated arthritis) and therapy (presence or absence of methotrexate, duration of therapy and doses). The research was conducted twice (the first - without additional intake of vitamin D, the second - after its 3-month supplementation of 2,000 IU). The serum level of vitamin D was measured through blood test by chemiluminescence method. Results. The average level of vitamin D was 22.26 ± 2.53 ng/ml. Dependence on gender and variant of the disease at the first stage of research was not found. Children under 6 years of age had a higher vitamin D status than older individuals (p < 0.05). At the second stage of research, the level of vitamin D in the general group of patients was 27.61 ± 3.56 ng/ml that proves a significant rise (p < 0.05). Male patients had a significant positive dynamics in comparison with female patients (p < 0.05). Vitamin D levels in little children increased to the optimal level. Positive changes in vitamin D status were found in patients with oligoarticular JIA (p < 0.05) in contrast to those with other variants of the disease. Patients who received methotrexate showed the better response to vitamin D intake than children who were not treated (p < 0.05). Positive dynamics was also observed in patients who were treated with methotrexate for no more than 2 years (p < 0.05). But the optimal status of vitamin D was achieved only in those who received basic therapy for no more than 6 months. The patients whose doses of methotrexate were less than 10 mg/m2/week have not showed the dynamics, in contrast to the subjects who received methotrexate at a dose of 10-15 mg/m2/week (p < 0.05). Conclusions. Children with JIA, who are older than 6 years; suffer from polyarthritis and undifferentiated JIA; whose duration of disease is more than 2 years; who receives methotrexate therapy over 6 months or at a dose below 10 mg/m2/week, have an insufficient response to vitamin D supplementation. Such patients require increasing the doses of vitamin D supplementation for both prophylactic and therapeutic purposes.